First Studies for the Development of Computational Tools for the Design of Liquid Metal Electromagnetic Pumps - Maidana C. (2017)
© 2016 Liquid alloy systems have a high degree of thermal conductivity, far superior to ordinary nonmetallic liquids and inherent high densities and electrical conductivities. This results in the use of these materials for specific heat conducting and dissipation applications for the nuclear and space sectors. Uniquely, they can be used to conduct heat and electricity between nonmetallic and metallic surfaces. The motion of liquid metals in strong magnetic fields generally induces electric currents, which, while interacting with the magnetic field, produce electromagnetic forces. Electromagnetic pumps exploit the fact that liquid metals are conducting fluids capable of carrying currents, which is a source of electromagnetic fields useful for pumping and diagnostics. The coupling between the electromagnetics and thermo-fluid mechanical phenomena and the determination of its geometry and electrical configuration, gives rise to complex engineering magnetohydrodynamics problems. The development of tools to model, characterize, design, and build liquid metal thermo-magnetic systems for space, nuclear, and industrial applications are of primordial importance and represent a cross-cutting technology that can provide unique design and development capabilities as well as a better understanding of the physics behind the magneto-hydrodynamics of liquid metals. First studies for the development of computational tools for the design of liquid metal electromagnetic pumps are discussed.